(3EVGAI GdQGehS aj EaGVI GdfGehS Ydi EaGVI GdbGehSs - (3GdaGSj, eMeO Hf ehSi, J(B1170(3g`s
(3ChdgG (B:s
(3fGbU GdChd , hChdg(B: (3Cj oQH GeQCI OHjGfjI ChUJ HfjgG hCeQJge Cf jcKQhG ef gPjf GdTjFjf hGdEcKGQ ef CNPgGs
(3BNQgG (B:s
(3fGbU GdBNQ, hBNQg(B: (3Ke Efg hbY aj TQhM GdTaG NdGa aj VHW ghPI abGd GdHQgGf GdMdHj(B: (3Efg HGdaJM ceGRe Hg GdLhgQj hghs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: 3 / 374s
(3gOjI GdYGQajf(B: 2 / 331s
(3EjVGM Gdecfhf(B: 1 / 94s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GddZIs